Pengembangan Media Pembelajaran Math Card (Kartu Matematika) Dalam Pembelajaran Matematika Materi Eksponen, SPLDV, Aritmatika - Andika M. Faris; Damar Wisnu Saputro; Dina Rubiati (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
Math Card is a card-based board game that contains questions for mathematics learning media. The purpose of the Math Card is to make it easier and more interesting for students in math lessons to make it more fun. This research uses the ADDIE method, namely analysis, design, development, implementation, and evaluation. At the analysis stage, analysis is carried out related to material needs by following per under the syllabus/curriculum and design needs to get design results that attract the attention of students. At the design stage, the design is carried out according to the needs of the Math Card, namely by designing cards, packaging, guidebooks, and game boards. The development stage is to develop the results of the material and design, namely compiling questions according to the syllabus and printing products. The implementation stage is to conduct trials for grade 10 SMK students in the classroom. The last is the evaluation stage, namely by improving and perfecting the Math Card learning method to be more effective and efficient.